Metode Dalam Memahami Hadis Studi Atas Pemikiran Tengku Muhammad Hasbie Ash-Shiddieqy - Fadiya, Adinda Nurul; Is, Fadhilah (UIN Sumatera Utara Medan, 2024)
This research aims to find out methods of understanding hadith in Indonesia and examine the thoughts of one of the hadith scholars in Indonesia, namely T.M Hasbie Ash-Shiddieqy, to study the methods used in understanding a hadith. This type of research is qualitative research using data analysis techniques. This research method is also included in library research. The data sources in this research are the works of T.M Hasbie in the field of hadith and also utilize data sources related to this scientific work, namely books, journals, articles and so on. The results of this research are that in understanding hadith, T.M. Hasbie uses several steps and methods, namely understanding hadiths with instructions from the Holly Qor‟an, interpreting abstruse hadiths, referring to various references and using several approaches which include historical, linguistic, scientific and health approaches.